The better half – asymmetric star formation due to ram pressure in the EAGLE simulations. Issue 4 (7th February 2020) - Troncoso-Iribarren, P; Padilla, N; Santander, C; Lagos, C D P; García-Lambas, D; Rodríguez, S; Contreras, S
ABSTRACT: We use the EAGLE simulations to study the effects of the intracluster medium on the spatially resolved star formation activity in galaxies. We study three cases of galaxy asymmetry dividing each galaxy into two halves using the plane (i) perpendicular to the velocity direction, differentiating the galaxy part approaching the cluster centre, hereafter dubbed the 'leading half', and the opposite 'trailing half'; (ii) perpendicular to the radial position of the satellite to the centre of the cluster; and (iii) that maximizes the star formation rate (SFR ) difference between the two halves. For (i), we find an enhancement of the SFR, star formation efficiency, and interstellar medium pressure in the leading half with respect to the trailing one and normal star-forming galaxies in the EAGLE simulation, and a clear overabundance of gas particles in their trailing. These results suggest that ram pressure is boosting the star formation by gas compression in the leading half, and transporting the gas to the trailing half. This effect is more pronounced in satellites of intermediate stellar masses 10^9.5\!-\!10^10.5 M_, with gas masses above 10^9 M_, and located within one virial radius or in the most massive clusters. In (iii), we find an alignment between the velocity and the vector perpendicular to the plane that maximizes the SFR difference between the two halves. It suggests that finding this plane in real galaxies can provide an insight into the velocity direction.